KENALI GULA SEJAK DINI MELALUI EDUKASI GAYA HIDUP SEHAT UNTUK CEGAH DIABETES DI KOMUNITAS - Jabbar, Asriullah; Nasrudin, Nasrudin; Fitrawan, La Ode Muhammad; Ansyar, May Nurmiati; Saputri, Desmy Elviyanti Dwi; Fitri, Devi Yulia; Naari, Asnarwaty; Bahrul, Hartina; Kana, Febrina; Haofu, La Ode Muhammad Hidayat; Fildayanti, Nunung; Mubarak, Mubarak; Y, Muhammad Ilyas; Juwita, Diana (MAJU : Indonesian Journal of Community Empowerment, 2025)
Diabetes mellitus is a growing public health concern influenced by excessive sugar consumption, unhealthy lifestyle patterns, and low awareness of early detection. This community service activity aimed to enhance the knowledge and awareness of residents in Kambu Village, Kendari City regarding diabetes prevention. The program consisted of health education on sugar intake and diabetes risks, group exercise sessions, distribution of educational materials, and free random blood glucose screenings. A total of 43 participants took part in the screening, with 41 individuals (95.35%) demonstrating normal glucose levels and 2 individuals (4.65%) showing elevated levels and being advised to undergo further medical evaluation. This activity successfully improved community understanding of diabetes risk factors and the importance of adopting healthy lifestyle practices. Overall, the program contributed positively to strengthening health literacy and encouraging preventive behaviors to reduce the risk of diabetes within the community.